Increased Fatigue Response to Augmented Deceptive Feedback during Cycling Time Trial - Ducrocq, Guillaume P; Hureau, Thomas J; Meste, Olivier; Blain, Grégory M (Medicine and science in sports and exercise, 2017)
This study aimed to investigate the effect of different magnitudes of deception on performance and exercise-induced fatigue during cycling time trial. After three familiarization visits, three women and eight men performed three 5-km cycling time trials while following a simulated dynamic avatar reproducing either 100% (5K100%), 102% (5K102%), or 105% (5K105%) of the subject's previous fastest trial. Quadriceps muscle activation was quantified with surface electromyography. Fatigue was quantified by preexercise to postexercise (10 s through 15 min recovery) changes in quadriceps maximal voluntary contraction (MVC) force, potentiated twitch force evoked by electrical femoral nerve stimulation (QTSingle) and voluntary activation (VA, twitch interpolation technique). Greater quadriceps muscle activation in 5K102% versus 5K100% (12% ± 11%) was found in parallel with a 5% ± 2% and 2% ± 1% improvement in power output and completion time, respectively (P < 0.01). Exercise-induced reduction in MVC force and VA were 14% ± 19% and 28% ± 31% greater at exercise termination (at 10 s), whereas QTSingle recovery (from 10 s to 15 min) was 5% ± 5% less in 5K102% versus 5K100% (P < 0.01). No difference in performance or fatigue indices measured at exercise termination was found between 5K100% and 5K105%. Muscle activation and performance improvements during a deceptive cycling time trial were achieved only with a 2% magnitude of deception and were associated with a further impairment in MVC force, QTSingle recovery and VA compared to control. Performance improvement during cycling time trial with augmented deceptive feedback therefore resulted in exacerbated exercise-induced peripheral and central fatigue.